A set of Yarrowia lipolytica CRISPR/Cas9 vectors for exploiting wild-type strain diversity - Larroude, Macarena; Trabelsi, Heykel; Nicaud, Jean-Marc; Rossignol, Tristan (Biotechnology letters, 2020)
Objectives The construction and validation of a set of Yarrowia lipolytica CRISPR/Cas9 vectors containing six different markers that allows virtually any genetic background to be edited, including those of wild-type strains. Results Using the Golden Gate method, we assembled a set of six CRISPR/Cas9 vectors, each containing a different selection marker, to be used for editing the genome of the industrial yeast Y. lipolytica . This vector set is available via Addgene. Any guide RNA (gRNA) sequence can be easily and rapidly introduced in any of these vectors using Golden Gate assembly. We successfully edited six different genes in a variety of genetic backgrounds, including those of wild-type strains, with five of the six vectors. Use of these vectors strongly improved homologous recombination and cassette integration at a specific locus. Conclusions We have created a versatile and modular set of CRISPR/Cas9 vectors that will allow any Y. lipolytica strain to be rapidly edited; this tool will facilitate experimentation with any prototroph wild-type strains displaying interesting features.